(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The management of dental caries in pediatric populations has undergone a significant paradigm shift, transitioning from traditional invasive restorative procedures toward a biological model centered on prevention and Minimally Invasive Dentistry (MID). This evolution is driven by an enhanced understanding of the demineralization-remineralization cycle and the development of bioactive materials. This article provides an in-depth analysis of primary prevention strategies, including the role of the oral microbiome, salivary buffering systems, and the application of silver diamine fluoride (SDF) and resin infiltration. Furthermore, it evaluates the efficacy of Atraumatic Restorative Treatment (ART) and the Hall Technique in preserving primary dentition. By prioritizing tissue conservation and psychological management, MID aims to improve the long-term oral health trajectory of children while minimizing dental anxiety and clinical complications.